Double grouping-based group handover scheme for mega LEO satellite networks - Hongtao, Zhu; Zhenyong, Wang; Dezhi, Li; Mingchuan, Yang; Qing, Guo (China communications, 2025)
The rapid development of mega low earth orbit (LEO) satellite networks is expected to have a significant impact on 6G networks. Unlike terrestrial networks, due to the high-speed movement of satellites, users will frequently hand over between satellites even if their positions remain unchanged. Furthermore, the extensive coverage characteristic of satellites leads to massive users executing handovers simultaneously. To address these challenges, we propose a novel double grouping-based group handover scheme (DGGH) specifically tailored for mega LEO satellite networks. First, we develop a user grouping strategy based on beam-limited hierarchical clustering to divide users into distinct groups. Next, we reframe the challenge of managing multiple users' simultaneous handovers as a single-objective optimization problem, solving it with a satellite grouping strategy that leverages the accuracy of greedy algorithms and the simplicity of dynamic programming. Additionally, we develop a group handover algorithm based on minimal handover waiting time to improve the satellite grouping process further. The detailed steps of the DGGH scheme's handover procedure are meticulously outlined. Comprehensive simulations show that the proposed DGGH scheme outperforms single-user handover schemes in terms of handover signaling over-head and handover success rate.